How Accurate Is Diagnosis of Congenital Anomalies Made by Family Physicians? - Hossein Mashhadi Abdolahi; Mohammad Hassan Kargar Maher; Majid Karamouz; Farzaneh Afsharnia; Hossein Khosroshahi; Saeed Dastgiri (Health Promotion Perspectives, 2014)
Background: Although family physicians have a key role in clinical management of many diseases and in community health, the accuracy of the diagnosis for congenital anomalies by family physicians still needs more investigations. The aim of this study was to assess the accuracy of family physicians in case detec-tion and diagnosis of congenital anomalies in rural areas, northwest of Iran. Methods: In a community-based study of 22500 children born between 2004 and 2012, all 172 cases of congenital anomalies diagnosed by family physicians were assessed by a qualified pediatrician in 47 health houses in rural areas of Tabriz District, northwest Iran. A group of 531 children was compared as con-trol subjects. Results: The overall sensitivity and specificity of family physicians‟ diagnosis for congenital anomalies were estimated 98% (95% Confidence Interval (CI): 95.9 to 100) and 100% (95% CI: 99.3 to 100), respectively. Sensitivity for diagnosis of congenital heart diseases was 97% (95% CI: 93 to 100), and for genitourinary tract, it was 86% (95% CI: 59 to 100). Specificity was estimated 100% for both groups of heart and genitourinary tract anomalies. Conclusion: The performance of family physicians was found accurate enough in the diagnosis of congenital anomalies. Health care system may consider family physician program as an effective approach to detect and clinical management of congenital anomalies.